2009
DOI: 10.1007/s11783-009-0035-2
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of methyl orange using ZnO/TiO2 composites

Abstract: ZnO/TiO 2 composites were synthesized by using the solvothermal method and ultrasonic precipitation followed by heat treatment in order to investigate their photocatalytic degradation of methyl orange (MO) in aqueous suspension under UV irradiation. The composition and surface structure of the catalyst were characterized by X-ray diffraction (XRD), field emission scanning electron microscope (FE-SEM), and transmission electron microscopy (TEM). The degradation efficiencies of MO at various pH values were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 32 publications
1
34
0
1
Order By: Relevance
“…An initial concentration of 1x10 -5 M was used and the experiments were carried out at pH 4, 7 and 9.6 with γ within the range γ = 0.07 -1.00. Methyl orange showed a steady rate of degradation at all experimental conditions because the reaction pathway involves unstable intermediates that are less reactive than methyl orange and present in low concentrations [32,35]. A 100 percent degradation of the dye was observed before the total reaction time elapsed for pH 4 and 7 at γ = 0.73 and γ = 1 respectively ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…An initial concentration of 1x10 -5 M was used and the experiments were carried out at pH 4, 7 and 9.6 with γ within the range γ = 0.07 -1.00. Methyl orange showed a steady rate of degradation at all experimental conditions because the reaction pathway involves unstable intermediates that are less reactive than methyl orange and present in low concentrations [32,35]. A 100 percent degradation of the dye was observed before the total reaction time elapsed for pH 4 and 7 at γ = 0.73 and γ = 1 respectively ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…TiO 2 /diatomite composite shows 90 % degradation of MO in 90 min under UV light. If ZnO nanoparticle is combined with TiO 2 instead of diatomite, 87.68 % degradation of MO is achieved in 60 min under UV irradiation (Ge et al 2009;Xia et al 2014). Among these four nanocomposites, ZnO/ TiO 2 composite holds best for the degradation of methyl orange.…”
Section: Degradation Of Textile Dyesmentioning
confidence: 99%
“…The electronic structure is characterized by the filled valence band and the empty conduction band. In TiO 2 -ZnO composites, the electron transfers from the conduction band of ZnO to the conduction band of TiO 2 under illumination and conversely, the holes transfers from the valence band of TiO 2 to the valence band of ZnO, decreasing the pairs' recombination rate; this charge separation effectively increases the lifetime of the charge carriers and enhances the efficiency of the interfacial charge transfer to adsorbed substrates [8].…”
Section: Emm-fm2011mentioning
confidence: 99%
“…It will be shown that the photocatalytic properties of TiO 2 can be improved in the two cases. It is worth noting that both semiconductors ITO and ZnO were reported to act as photocatalysts [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%